Accelerability vs. Scalability: R&D Investment Under Financial Constraints and Competition - Lin, Danmo (Management Science, 2023)
I develop a continuous-time model to examine how the interaction between competition and financial constraints affects firms’ research and development (R&D) strategies. The model integrates two key characteristics of R&D investment: accelerability (i.e., higher R&D intensity leads to faster discovery) and scalability (i.e., higher R&D intensity leads to higher project payoff). I find that firms react strategically to their rivals’ financial constraints when making investment decisions in a duopoly R&D race. In particular, firms respond positively to the R&D intensity of an unconstrained rival, while they respond in a hump-shaped fashion to the R&D intensity of a constrained rival. As a result, a constrained firm can pre-empt an unconstrained competitor in market equilibrium. Accelerability is necessary for such pre-emption to occur, and scalability generally reduces its likelihood. Comparison with a monopoly benchmark shows that the economic mechanism differs from over-investment induced by financial constraints alone. The model also generates new implications regarding how project characteristics and cash flow risks impact R&D decisions. This paper was accepted by Gustavo Manso, finance. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2022.4503 .